Associations of lifetime prevalence of homelessness with risky sex, sexual victimization, depressive symptoms, and suicidality among youth in Kampala, Uganda. (July 2021) - Lyons, Matthew; Swahn, Monica Haavisto; Whitaker, Daniel; Brown, Jessica Rogers; Kasper, Jim; Culbreth, Rachel
Homelessness poses serious health risks, and those risks may be exacerbated among slum-dwelling youth in the developing world. We administered a cross-sectional survey to youth receiving services from a community organization in Kampala, Uganda. This secondary analysis explores the relationships between homelessness and various health outcomes. We also explored possible moderating relationships between neighborhood support, homelessness, and health. Logistic regression and t -tests were used to model these relationships. Homelessness was associated with all outcomes analyzed, with youth who reported having been homeless having higher odds of reporting poor health (odds ratio [OR] = 12.4; 95% confidence interval [CI] = 6.43, 23.92), higher odds of HIV infection (OR = 1.941; 95% CI = 1.274, 2.958), and higher odds of experiencing rape (OR = 3.459; 95% CI = 2.4, 4.987). No moderation by neighborhood support was observed, though this may be due to low variability. Homelessness warrants specific investigative attention due to its strong association with a broad range of negative health outcomes among slum-dwelling youth. Interventions targeting the specific health risks faced by homeless youth in the developing world may improve social welfare service delivery.